Taurine/Pilocarpine Interaction in the Malnourished Rat Brain: A Behavioral, Electrophysiological, and Immunohistochemical Analysis - Francisco, Elian da Silva; Mendes-da-Silva, Rosângela Figueiredo; Castro, Cássia Borges Lima de; Soares, Geórgia de Sousa Ferreira; Guedes, Rubem Carlos Araújo (Frontiers in Neuroscience, 2019)
This study aimed to evaluate the possible protective role of taurine on anxiety-like behavior, brain electrical activity and glial cell immunoreactivity in well-nourished and malnourished rats that were treated with a subconvulsing dose of pilocarpine. Newborn Wistar rats were subjected to normal or unfavorable lactation conditions, represented by the suckling of litters with nine or fifteen pups, resulting in well-nourished and malnourished animals, respectively. Each nutritional group was split into five subgroups that were treated from postnatal day (PND) 35 to 55 with 300 mg/kg/day of taurine + 45 mg/kg/day of pilocarpine (group T+P), taurine only (group T), pilocarpine only (group P), vehicle control (group V), or not treated control (group naïve; Nv). At PND56-58, the groups were subjected to the elevated plus-maze behavioral tests. Glycemia was measured on PND59. Between PND60 and PND65, the cortical spreading depression (CSD) was recorded in the cerebral cortex, and the levels of malondialdehyde and microglial and astrocyte immunoreactivity were evaluated in the cortex and hippocampus. Our data indicate that treatment with taurine and pilocarpine resulted in anxiolytic-like and anxiogenic behavior, respectively, and that nutritional deficiency modulated these effects. Both treatments decelerated CSD propagation and modulated GFAP- and Iba1-containing glial cells. Pilocarpine reduced body weight and glycemia, and administration of taurine was not able to attenuate the effects of pilocarpine. The molecular mechanisms underlying taurine action on behavioral and electrophysiological parameters in the normal and altered brain remains to be further explored.